The Effect of Work Motivation and Discipline on Employee Work Productivity at PT. Tbk Star Insurance in Jakarta - Wahyitno Wahyitno; Umi Nariawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (Peneliti.net, 2022)
This study aims to determine the effect of motivation and work discipline on the work productivity of employees at PT. Asuransi Bintang Tbk in Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that motivation has a significant effect on employee productivity by 4.31%, hypothesis testing is obtained t count > t table or (6.628 > 2.002). Work Discipline has a significant effect on employee productivity by 40.7%, hypothesis testing is obtained t count > t table or (6.311 > 2.002). Motivation and work discipline simultaneously have a significant effect on employee productivity with the regression equation Y = 9.939 + 0.395X1 + 0.360X2 and the contribution of the effect is 53.0%, hypothesis testing is obtained F count > F table or (32.194 > 2.770.